Forebrain epileptiform activity is not required for seizure-induced apnea in a mouse model of Scn8a epilepsy - Wenker, Ian C.; Boscia, Alexis R.; Lewis, Christine; Tariq, Anas; Miralles, Raquel; Hanflink, Jessica C.; Saraf, Priyanka; Patel, Manoj K. (Frontiers in Neural Circuits, 2022)
Sudden unexpected death in epilepsy (SUDEP) accounts for the deaths of 8 to 17 % of patients with epilepsy. Although the mechanisms of SUDEP are essentially unknown, one proposed mechanism is respiratory arrest initiated by a convulsive seizure. In mice, we have previously observed that extended apnea occurs during the tonic phase of seizures. Although often survived, tonic seizures became fatal when breathing did not immediately recover postictally. We also found that respiratory muscles were tonically contracted during the apnea, suggesting that muscle contraction could be the cause of apnea. In the present study, we tested the hypothesis that pyramidal neurons of the motor cortex drive motor units during the tonic phase, which produces apnea. Mice harboring the patient-derived N1768D point mutation of an Scn8a allele were crossed with transgenic mice such that inhibitory DREADD receptors were selectively expressed in excitatory forebrain neurons. We then triggered audiogenic and hippocampal (HC) stimulated seizures under control conditions and when excitatory forebrain neurons were inhibited with the synthetic ligand Clozapine-N-Oxide (CNO). We found that inhibition with CNO was sufficient to increase seizure threshold of HC stimulated, but not audiogenic, seizures. In addition, regardless of seizure type, CNO nearly eliminated epileptiform activity that occurred proximal to the tonic phase; however, the seizure behaviors, notably the tonic phase and concomitant apnea, were unchanged. We interpret these results to indicate that while cortical neurons are likely critical for epileptogenesis and seizure initiation, the behavioral manifestations of tonic seizures are generated by neural circuitry in the mid- and/or hindbrain.